Agresión y empatía en un grupo de niños y niñas diagnosticados con trastorno negativista desafiante (2015)
ABSTRACT: This study aimed to explore the relationships between the levels of aggression (physical, verbal, anger and hostility) and empathy in a group of school children between 7 and 11 years old in the city of Medellin (Colombia), diagnosed Oppositional Defiant Disorder. A reduced version of the Buss-Perry Aggression Questionnaire in Spanish was used to assess aggression; and a test about the type of stare and the Interpersonal Reactivity Index were administered to assess empathy. The results indicated a higher ranking on physical aggression in men in relation to women. It was found an existing relationship between aggression and some empathy levels (direct, as in the case of the number of success in the type of stare test, and opposite, with the number of errors in the same test); both relationships were significant.